PSYCHOLOGICAL-PEDAGOGICAL FOUNDATIONS OF DEVELOPING SCIENTIFIC-PEDAGOGICAL COMPETENCIES AT THE MASTER'S LEVEL IN HIGHER EDUCATION - Khaydarova Makhliyo Khabibullayevna (American Journals, 2025)
The article is dedicated to the psychological-pedagogical foundations of developing scientific-pedagogical competencies at the master's level in higher education. It analyzes the psychological patterns in the formation and development of competencies—such as motivational components, self-assessment, cognitive and emotional processes— as well as pedagogical foundations, including the design of educational content, individualization, practical application, and the use of innovative technologies. The stepwise complexity of scientific research competencies in master's programs, their qualitative transformation from the bachelor's level, and characteristics of heterochrony and cumulativity are examined. Psychological-pedagogical approaches are emphasized as serving to foster students' abilities to independently develop research programs, make decisions, and engage in reflection.
Keywords: Master's degree, scientific-pedagogical competencies, psychological foundations, pedagogical foundations, development, motivation, practice.